2009
DOI: 10.1073/pnas.0903360106
|View full text |Cite
|
Sign up to set email alerts
|

A role for galanin in human and experimental inflammatory demyelination

Abstract: The neuropeptide galanin is widely expressed by many differing subsets of neurons in the nervous system. There is a marked upregulation in the levels of the peptide in a variety of nerve injury models and in the basal forebrain of humans with Alzheimer's disease. Here we demonstrate that galanin expression is specifically and markedly upregulated in microglia both in multiple sclerosis (MS) lesions and shadow plaques. Galanin expression is also upregulated in the experimental autoimmune encephalomyelitis (EAE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 47 publications
(57 reference statements)
1
43
0
Order By: Relevance
“…Our findings further support the identification by Raison and Miller of single nucleotide polymorphisms in cholinergic-related genes associated with major depression (24)(25)(26)(27)(28) and with the beneficial use of vaccination to reduce inflammation in successful independent aging (29). Recently we found that anxiety (which shares many symptoms with depression) ignites exacerbation of pre-existing neuro-immune risks (5), compatible with our previous reports of co-increasing severity of symptoms, shrinkage of the hippocampus and inflammation biomarkers in patients with post-traumatic stress disorder, who tend to be depressed (30).…”
Section: Discussionsupporting
confidence: 78%
“…Our findings further support the identification by Raison and Miller of single nucleotide polymorphisms in cholinergic-related genes associated with major depression (24)(25)(26)(27)(28) and with the beneficial use of vaccination to reduce inflammation in successful independent aging (29). Recently we found that anxiety (which shares many symptoms with depression) ignites exacerbation of pre-existing neuro-immune risks (5), compatible with our previous reports of co-increasing severity of symptoms, shrinkage of the hippocampus and inflammation biomarkers in patients with post-traumatic stress disorder, who tend to be depressed (30).…”
Section: Discussionsupporting
confidence: 78%
“…The preparation and immunization of the synthetic cannabinoid R(ϩ)WIN55,212-2 (Sigma) was modified from previous studies (30 Histology-Spinal cords were dissected and fixed in 10% formaldehyde saline. Spinal cords were sectioned and stained with hematoxylin and eosin for inflammatory scoring (31). Inflammatory scores were as follows: 0, no inflammatory cells; 1, a few scattered inflammatory cells; 2, perivascular cuffing; 3, perivascular cuffing with extensions into adjacent parenchyma, or parenchymal infiltration without obvious cuffing.…”
Section: Methodsmentioning
confidence: 99%
“…The BV2 mouse microglia cell line and cultured rat microglial cells solely express GAL 2 (Su et al, 2003;Ifuku et al, 2011), which mediates galanin-induced cell migration and upregulation of class II major histocompatibility complex expression in these innate immune brain cells (Ifuku et al, 2011). Microglial cells also participate in the events leading to multiple sclerosis (Weissert, 2013), and a recent study detected a marked upregulation of galanin expression in microglia associated with multiple sclerosis lesions in postmortem brain tissue from chronic multiple sclerosis patients (Wraith et al, 2009). …”
Section: Galanin Family Peptides and Receptorsmentioning
confidence: 99%
“…There is also good evidence for a role for galanin signaling in processes of myelination and responses to myelin injury (Wraith et al, 2009;Zhang et al, 2012) along with proliferation, differentiation, and/or migration of oligodendrocyte precursor cells Ubink et al, 2003;Butzkueven and Gundlach, 2010) and neural stem and progenitor cells (the latter topic is covered in section VIII). It is highly likely that ongoing research in these areas will produce further evidence of the pleiotropic actions of galanin and the associated receptor mechanisms.…”
Section: Galanin Family Peptides and Receptorsmentioning
confidence: 99%
See 1 more Smart Citation